PENGENALAN BERHITUNG MATEMATIKA PADA ANAK USIA DINI DI RA NURUL JADID - Anis Hidayati (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
Mathematics learning in early childhood education (PAUD) begins gradually by introducing numbers through counting tangible objects or real-life experiences that children encounter in their daily lives, based on their observations. The introduction of mathematical concepts to children should be done using simple language and enjoyable methods. However, many teachers still introduce mathematics to young children using conventional methods, leading to students' disinterest in learning mathematics. Therefore, researchers conducted classroom action research on the theme of introducing counting to early childhood students, conducted with B3 level students at RA Nurul Jadid, consisting of 12 students. Data was collected through observation techniques, tests, documentation, and field notes. Quantitative data were analyzed using calculation formulas on the test questions, while qualitative data were analyzed using triangulation. The results of this study revealed that introducing counting in mathematics to RA Nurul Jadid students through games using an egg carton resulted in improved learning outcomes for the children.